Модели когнитивных архитектур и процессов на основе парадигмы предельных обобщений - Прокопчук, Ю.А. (Кибернетика и вычислительная техника, 2013)
Предложена конструктивная версия механизма предельных обобщений и полимодельной дополнительности как парадигмального базиса и показана ее продуктивность при решении ряда теоретико-прикладных проблем когнитивной науки. Построены формальные модели спонтанных идеальных процессов самоорганизации и формирования имплицитного опыта. Запропоновано конструктивну версію механізму граничних узагальнень і полімодельної додатковості як парадигмального базису та показана її продуктивність при рішенні теоретико-прикладних проблем когнітивної науки. Побудовано формальні моделі спонтанних ідеальних процесів самоорганізації та формування імпліцитного досвіду. Among the open problems in the cognitive system theory there are the comprehension and simulation of empirical creative thinking processes, of the ability to single out order parameters in the development of complex situations of reality, of implicit and explicit experience formation, and of phenomena of ideal. This paper presents the author’s approach to the solution of the above problems, which is based on a paradigm of limiting generalizations. The proposed models are based on three interrelated information–energy entities: meaning, domain, and sketch digraphs, dynamic system patterns, and structural energy. System patterns form structural energy transfer channels. These elemental entities are in permanent motion due to their structural instability, thus setting up intrinsic motive forces and providing self-motion. Formal models of spontaneous cognitive dynamics are constructed. The constructed models of dynamics feature high robustness.